DOP89 Effects of ferric derisomaltose and ferric carboxymaltose on hypophosphatemia in iron-deficiency anaemia due to Inflammatory Bowel Disease: A Phase IV randomised clinical trial. (27th May 2021) - Zoller, H; Wolf, M; Blumenstein, I; Primas, C; Lindgren, S; Thomsen, L L; Reinisch, W; Iqbal, T
Abstract: Background: Intravenous iron can correct iron deficiency anaemia (IDA) in inflammatory bowel disease (IBD). Certain formulations are associated with hypophosphatemia, but this has not previously been investigated in a randomised clinical trial in IBD. The aim of this randomised, double-blind trial was to compare the risk of hypophosphatemia with ferric derisomaltose/iron isomaltoside 1000 (FDI) vs ferric carboxymaltose (FCM) in patients with IDA due to IBD. Methods: Adults with IBD and IDA (haemoglobin [Hb] <13g/dL; s -ferritin ≤100ng/mL) who were unsuitable for oral iron treatment were recruited at outpatient clinics in 5 European countries. Patients were randomised 1:1 to FDI or FCM (1000mg at baseline and 500 or 1000mg at Week 5 based on weight and iron need at baseline). The primary endpoint was the incidence of hypophosphatemia ( s -phosphate <2.0mg/dL) from baseline to Week 5. Additional endpoints included biomarkers of bone and mineral metabolism, Hb concentrations, fatigue score, and adverse events (AEs). Results: Of 97 patients enrolled (mean age 42.1 years; 52.6% female; 39.2% Crohn's disease; 60.8% ulcerative colitis), 48 received FDI and 49 FCM. The incidence of hypophosphatemia was significantly lower for FDI than FCM (8.3% vs. 51.0%; p<0.0001). After the first dose, biomarker responses (least squares mean change from baseline) were significantly less pronounced after FDI than FCM: s -phosphate decreased less with FDI than FCM, with a nadir at Week 1 (FDI, -0.49mg/dL; FCM, -1.33mg/dL; p<0.0001); urinary fractional excretion of phosphate increased less at Week 1 (FDI, 2.58%; FCM, 9.22%; p=0.0021); intact fibroblast growth factor 23 increased markedly over the first day only with FCM (FDI, -8.54pg/mL; FCM, 149.31pg/mL; p<0.0001); 1, 25-dihydroxyvitamin D decreased less with FDI than FCM, with a nadir at Week 1 (FDI, -16.39pg/mL; FCM, -30.83pg/mL; p<0.0001); parathyroid hormone increased only in the FCM group, with a peak at Week 2 (FDI, -2.22pg/mL; FCM, 14.28pg/mL; p=0.011). Bone-specific alkaline phosphatase increased more with FCM than FDI at Week 2 (p=0.0025), with the difference persisting at Week 10 (p=0.0041). Hb increased in both groups and were comparable at all time points. Improvements from baseline in fatigue score were greater for FDI than FCM at Weeks 5 and 7 (both p<0.01). Incidence of AEs were comparable (FDI, 91.7%; FCM, 89.8%). Conclusion: In IDA due to IBD, FDI resulted in significantly lower incidence of hypophosphatemia than FCM. FDI and FCM lead to similar increases in Hb concentration. In contrast to FDI, FCM treatment led to persistent changes in bone biomarkers, suggesting possible long-term adverse effects on bone health. ClinicalTrials.gov Identifier: NCT03466983. Supported by Pharmacosmos A/S (Holbæk, Denmark).